Primary Intestinal Lymphangiectasia diagnosed by Single-Balloon Enteroscopy - C Romero Mascarell; IK Araujo; I Ordás; H Briceno; D Monfort; C Rodriguez-de Miguel; A Ginés; G Fernández-Esparrach; M Cuatrecasas; J Llach; B González Suárez (Archives of Clinical Gastroenterology - Peertechz Publications, 2018)
Primary intestinal lymphangiectasia (PIL) is a rare protein losing gastroenteropathy that usually affects children and teenagers. There are only a few cases described in the literature. The diagnosis is confirmed by the presence of intestinal lymphangiectasia based on endoscopic findings and histology. We present a case of PIL diagnosed in a teenager patient, by Small Bowel Capsule Endoscopy (SBCE) and Single Balloon Enteroscopy (SBE).